Strategies In Teaching Vocabulary At The First Year In Smp N 2 Bringin, Kabupaten Semarang - Pamungkas, Sasa Astra (2012)
This research is aimed at describing the strategies used by the teacher, problem faced by the teacher, and problem solved by the teacherin teaching vocabulary. The writer uses descriptive qualitative to analyze the data. The data are taken from interview, observation and document. The subject of this study is the English teacher of SMP N 2 Bringin Kabupaten Semarang. The object of this study focuses on the process of teaching vocabulary to the first grade students in SMP N 2 Bringin Kabupaten Semarang. Based on the class observation, interview, and document, the writer draws some conclusion about the strategy by the teacher, problem faced and problem solved by the teacher. The strategies committed by the teacher are: (1) memorization, (2) synonym/antonym, (3) translating, and (4) fill in the blank. The problems faced by the teacher are: (1) classroom management, (2) student's motivation and (3) student's laziness. The problems solved by the teacher are: (1) she called the students who make noisy and asked them some questions about the material or she ordered the student who wasnoisy to go out, (2) the teacher gave advice and motivation about the importance of English subject and the importance to improve the vocabulary. Besides, the teacher also implemented another strategy by givingscore to the active students. The students also can consult the difficult materials with the teacher out of class, (3) the teacher gave new vocabulary that wrote in the whiteboard every meeting to improve their vocabulary. The strategies used by the teacher are good because the strategies can make the students more active. Besides that, the strategies used by the teacher can make the students interested in following theclass.